Divergent Mechanisms of Internode Elongation in Response to Far-Red in Two Rose Genotypes - Laurent Crespel; Camille Le Bras; Bénédicte Dubuc; Maria-Dolores Perez-Garcia; Esther Carrera; Aurélia Rolland; Rémi Gardet; Soulaiman Sakr (Plants)
The quality of potted ornamental plants depends on their architecture, which should be compact and branched. Among the techniques for controlling this architecture, LED lighting, by manipulating light quality, offers an effective means of regulating elongation and branching. In rose, the addition of far-red (FR) light stimulated branching but induced excessive stem elongation, i.e., internode elongation. However, some varieties remained insensitive to this effect, demonstrating phenotypic stability. This study investigated the underlying mechanisms of internode elongation in response to FR in two rose cultivars, ‘The Fairy’ (TF) and Knock Out® Radrazz (KO), selected for their respective architectural plasticity and stability to FR. In TF, exposure to FR induced elongation of internodes, driven by cell division, with an increase in gibberellin A4 (GA4) level and a reduction in defense hormones (salicylic acid and jasmonic acid; JA). In contrast, in KO, exposure to FR did not induce internode elongation but caused cell elongation. This effect was accompanied by a reduction in cell number, modulated by hormonal changes (particularly GA4 and JA) and the inhibition of Block of cell proliferation 1, thereby limiting cell division. A deeper understanding of the mechanisms underlying architectural stability might lead to developing strategies to produce compact, branched plants, regardless of environmental conditions.